Castanea bra / Nuramirah Megat Adnan ... [et al.] - Megat Adnan, Nuramirah; Abd Hamid, Hamimah; Iree, Cheryl; Mohamad Khatta, Alya Qistina; Zulkifly, Nur Nashwa; Amran, Nur Ain Humaira (2023)
The Castanea Bra is a technologically advanced innovation in intimate wear which is a bra that redefines design and comfort. This report discusses its development, addressing customer issues ranging from itching to breathability. The Castanea Bra, motivated by discomfort, is a ground-breaking solution that combines cooling materials and anti-microbial features. The methodology, which is based on a Consumer Trend Canvas, a Google Form survey, research, and observation, contributes to the evolution of the Malaysian intimate wear industry by aligning with changing customer expectations. Research and development were made systematically to produce a new and innovative product. The final outcome of the design was made by generating ideas during the brainstorming session. All resources were made use to gather all the information regarding the latest design and technology, issues, demands, and others to which they were finally screened out to filter and select the best and promising results. After it was all finalised, sketches of the design and features were made according to the gathered information before choosing the right materials. This innovation focuses primarily on the comfort for the women’s breasts of all sizes so that they can have a great experience upon wearing it daily. Finally, a market survey was made to learn more about our target market and validate our customers’ needs. In addition, concept testing was applied to obtain information and responses from the respondents. Furthermore, a building prototype of the Castanea Bra was sketched, showing the front view, back view, and the inside layer of the bra cup for a detailed look.